MOTIVATION AND LOCAL GOVERNMENT EMPLOYEES IN NIGERIA - Abbass, Isah Mohammed (European Scientific Journal, ESJ, 2012)
In every organization, whether large or small, governmental or non-governmental, employees work enthusiastically or with zeal and cooperate amongst themselvesand with the leadership to achieve the laid down objectives. This is primarily due to the job satisfaction they derive in the conduct of their routine activities. The local government system, within the so-called three tiers of governmental structure in Nigeria, is the neglected step-child in the entire governmental arrangement. The nexus between motivation and employees in the local government has beena neglected theme of study in Nigeria. In most cases, the condition of employment in the local governments has always been taken as given within the prevailing orthodoxy of governance. This papertherefore,attempts to explore the kinds of motivations whichthe employees of local government should be provided with:This is done within the context of institutional claims by these employers and how the validity of such claims, or the lack of it impact upon employees spirit and performance against set down goals, mission and vision of the organization.